2019
DOI: 10.5755/j01.ms.26.2.21286
|View full text |Cite
|
Sign up to set email alerts
|

The Preparation and Research on the Electromagnetic Shielding Effectiveness of T-ZnO@Ag/Silicone Rubber Composites

Abstract: This study first conducted surface modification of Ag-plated Tetrapod-like zinc oxide (T-ZnO) whiskers with the use of dopamine and prepared Ag-plated T-ZnO whiskers (T-ZnO@Ag) by means of chemical plating, in which AgNO3 solutions with different concentrations were used during the preparation. Micro-structures of the prepared T-ZnO@Ag powders were examined to evaluate the effect of AgNO3 concentration on Ag plating performance. Subsequently, conductive Si rubber samples were prepared, the T-ZnO@Ag powders wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…10,43 As electromagnetic waves enter the composite, numerous conductive flow networks composed of ZnO@AgNWs can decompose the electromagnetic wave energy, thus reducing the electromagnetic wave energy and enhancing its electromagnetic shielding performance. 44 By comparing the electromagnetic shielding mechanism of materials, EMI SE mechanism diagram of modified composite is drawn as shown in Figure 7. According to the previous analysis, the construction of ZnO@AgNWs composite conductive network makes the surface of composite form a thin conductive material network layer, which provides strong reflection and relatively large SE.…”
Section: The Electromagnetic Shielding Properties Of Zno@agnws/wpu/co...mentioning
confidence: 99%
“…10,43 As electromagnetic waves enter the composite, numerous conductive flow networks composed of ZnO@AgNWs can decompose the electromagnetic wave energy, thus reducing the electromagnetic wave energy and enhancing its electromagnetic shielding performance. 44 By comparing the electromagnetic shielding mechanism of materials, EMI SE mechanism diagram of modified composite is drawn as shown in Figure 7. According to the previous analysis, the construction of ZnO@AgNWs composite conductive network makes the surface of composite form a thin conductive material network layer, which provides strong reflection and relatively large SE.…”
Section: The Electromagnetic Shielding Properties Of Zno@agnws/wpu/co...mentioning
confidence: 99%
“…The presence of micropores further reduces its areal density, which is beneficial for its application as lightweight EMI shielding materials. Moreover, silicone rubber (SiR) possesses high flexibility compared with other polymer materials, [29,30] and it can be combined with Cuf to achieve the characteristics of low density and good flexibility of the composite materials. As far as we know, it is rarely reported that metal and polymer materials are macroscopically compounded through chemical bonds and mechanical interlocks.…”
Section: Introductionmentioning
confidence: 99%
“…According to the binary phase diagram of Mg-Li alloy [17], when the Li content is between 5.3 wt.% and 10.7 wt.%, the alloy shows a typical dual-phase structure, so it also has obvious advantages in electromagnetic shielding. When Al alloy is coated on Mg alloy, its plasticity and corrosion resistance can be improved through the complementary effects of various materials [18], and the addition of Al layer can improve the electrical conductivity of the material, which is similar to conductive coating materials [19]. Moreover, Al alloy and Mg alloy are both light metals, which will not deteriorate the shielding density of multilayered composite materials [20], in addition, the addition of the Al layer increases the number of alloy layers, strengthens the interface reflection, and is also conducive to electromagnetic shielding effectiveness.…”
Section: Introduction *mentioning
confidence: 99%